Endometrial immune markers are potential predictors of normal fertility and pregnancy after in vitro fertilization. (25th April 2017) - Kofod, Louise; Lindhard, Anette; Bzorek, Michael; Eriksen, Jens Ole; Larsen, Lise Grupe; Hviid, Thomas Vauvert F.
Abstract : Problem: Elucidating immune mechanisms in the endometrium, which lead to the success of implantation and pregnancy, is important in reproductive medicine. Studies of immune cell abundance have shown conflicting results, and the expression and importance of HLA class Ib proteins in pre‐implantation endometrium have not yet been investigated. Method of study: The study population consisted of four subgroups: a hydrosalpinx, a salpingectomy, an unexplained infertility, and a fertile control group. Endometrial samples were collected during the implantation window. Immune markers (CD56 + and CD16 + cells, FoxP3 + Tregs, HLA‐G, HLA‐F) were quantified in the samples. The outcome of the subsequent IVF treatment was recorded. Results: Increased CD56 + uNK cells and high HLA‐G expression served as predictor for successful pregnancy outcome. HLA‐F expression was positively correlated with uNK cells, being indirectly predictive for achieving pregnancy. Conclusion: Endometrial uNK cell abundance in the pre‐implantation endometrium seems to be important for normal fertility and pregnancy success, and they may be used as clinical markers to predict implantation success in IVF.